Schmerzkonzept einer kinderchirurgischen Klinik - Lange, Bettina; Wessel, Lucas (Monatsschrift Kinderheilkunde, 2012)
The principle of an anxiety and pain-free treatment necessitates, particularly in childhood, a standardized age-related pain management. The oral, rectal or i.v. administration of a sedative/analgesic in pediatric surgery is mostly accompanied by a great deal of stress for all involved and the alternative of general anesthesia is often not readily available or even not available at all. The high analgesic, anxiolytic and sedative potency of nitrous oxide has been known worldwide for a long time but the inhalative administration is not in general use as the approval as a ready to use pharmaceutical was only granted in Germany in 2008. Nitrous oxide is absorbed and eliminated through the lungs and because metabolism does not take place in the body fasting is unnecessary. Side effects can occur but are completely reversible at the end of the application.
Gesehen am 09.05.2018